An examination of the cycling performance and failure mechanisms in mechanically alloyed composites containing antimony metal, iron oxide, and carbon black. (1st November 2016) - Demko, Michael T.; Xun, Shidi; Kim, Sang-Hwan; Liu, Hansan; Mai, Thuy; Nguyen, Phu; Featherer, Robin; Lin, Xiaoping; Subramoney, Shekhar; Warrington, Keith
Graphical abstract: Highlights: Cycle lifetime is enhanced by the microstructure of the composite. Electrochemical properties are a superposition of the individual constituents. Cycle lifetime is ultimately limited by SEI instability and impedance growth. The volume change of the antimony is still ultimately responsible for SEI instability. Abstract: Composite anode materials prepared using high energy mechanical milling have exhibited stable cycling in several previous works. One such material, a composite of antimony metal, carbon black, and iron oxide, shows particular promise as a higher voltage alternative to graphite and silicon. This material can enable safe operation in applications requiring high charging rates while providing a lower voltage and higher capacity alternative to lithium titanate. However, the stringent requirements for commercializing new materials for lithium ion batteries can be a serious impediment for new materials reaching into this existing market. The key requirements investigated here are the capacity, 1 st cycle coulombic efficiency, hysteresis, and cycle lifetime. It is found that the combination of these materials with high energy milling can enhance the cycle lifetime of the individual constituent components, while the other properties behave as a simple superposition of the constituent components. This behavior is due to the intimate composite structure formed by the high energy milling. The failure of the electrochemical cell is primarily caused by the impedance growth of the material, which seems to be caused by instability of the SEI layer that forms on this volume changing material.